Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm studying some Calculus on my own. I get what appears to be the wrong answer for this one implicit differentiation exercise, and I don't know why.

I have to find $\frac {d^2 y}{dx^2}$ of $y^2-2x = 1-2y$. I calculate

$\frac{dy}{dx} = \frac{1}{1+y}$

and from there I get

$\frac {d^2 y}{dx^2} = \frac{-y'}{(1+y)^2} = -\frac{1}{(1+y)^3}$

Now, Wolfram Alpha tells me I got $f'$ right but $f''$ wrong. It says

$\frac{\delta^2y(x)}{\delta x^2} = - \frac{1}{2(1+x)(1+y)}$

WA hasn't steered me wrong so far. Pointers to where I'm going wrong would be appreciated.

share|cite|improve this question
$2(1+x)=y^2+2y+1=(y+1)^2$. – Did May 27 '12 at 10:52
up vote 4 down vote accepted

$$y^2-2x = 1-2y\tag{1}$$





$$y'' = \frac{(1)'(y+1)-(y+1)'(1)}{(y-1)^2}=\frac{-y'}{(y+1)^2}$$


As Didier pointed out in his comment, from $(1)$ we have:

$$y^2+2y\color{red}{+1} = 1+2x\color{red}{+1}$$

$$(y+1)^2 = 2(1+x)$$

So WA just substituted $(y+1)^2 $ with $2(1+x)$:


share|cite|improve this answer
Awesome. Thanks. :) – Apteris May 27 '12 at 12:33

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.